EVI1 induces myelodysplastic syndrome in mice - Buonamici, Silvia (American Society for Clinical Investigation, 2004)
Myelodysplasia is a hematological disease in which genomic abnormalities accumulate in a hematopoietic stem cell leading to severe pancytopenia, multilineage differentiation impairment, and bone marrow (BM) apoptosis. Mortality in the disease results from pancytopenia or transformation to acute myeloid leukemia. There are frequent cytogenetic abnormalities, including deletions of chromosomes 5, 7, or both. Recurring chromosomal translocations in myelodysplasia are rare, but the most frequent are the t(3;3)(q21;q26) and the inv(3)(q21q26), which lead to the inappropriate activation of the EVI1 gene located at 3q26. To better understand the role of EVI1 in this disease, we have generated a murine model of EVI1-positive myelodysplasia by BM infection and transplantation. We find that EVI1 induces a fatal disease of several stages that is characterized by severe pancytopenia. The disease does not progress to acute myeloid leukemia. Comparison of in vitro and in vivo results suggests that EVI1 acts at two levels. The immediate effects of EVI1 are hyperproliferation of BM cells and downregulation of EpoR and c-Mpl, which are important for terminal erythroid differentiation and platelet formation. These defects are not fatal, and the mice survive for about 10 months with compensated hematopoiesis. Over this time, compensation fails, and the mice succumb to fatal peripheral cytopenia.